A Comparative Study Between Local Anesthesia ( LA) and Brachial Plexus Block (BPB) for Arteriovenous Fistula (AVF) Creation (KYAMC Journal, 2025)
Background: Arteriovenous fistula creation is essential for hemodialysis in patients with end-stage renal disease. The choice between local anesthesia and brachial plexus block can impact clinical outcomes.Objective: To compare effectiveness, safety, and patient outcomes associated with local anesthesia (Group A) and brachial plexus block (Group B) in Arteriovenous fistula creation.Materials and Methods: A Cross-sectional study was conducted between September 2022 and June 2023 at the Department of Cardiac Anesthesia & CICU, Khwaja Yunus Ali Medical College & Hospital, Sirajganj. A total of 124 patients were equally divided into two groups: Group A (local anesthesia, n=62) and Group B (brachial plexus block, n=62). Pain levels (measured using a visual analog scale), surgical success rates, postoperative recovery times, and complications were analyzed. Statistical significance was determined using a p-value